An Investigation of the RNA Modification m6A and Its Regulatory Enzymes in Rat Brains Affected by Chronic Morphine Treatment and Withdrawal - Hronova, Anna; Pritulova, Eliska; Hejnova, Lucie; Novotny, Jiri (International journal of molecular sciences, 2025)
N6-methyladenosine (m6A) is one of the most prevalent methylated modifications of mRNA in eukaryotes. This reversible alteration can directly or indirectly influence biological functions, including RNA degradation, translation, and splicing. This study investigates the impact of chronic morphine administration and varying withdrawal durations (1 day, 1 week, 4 weeks, and 12 weeks) on the m6A modification levels in brain regions critical to addiction development and persistence. Our findings indicate that in the prefrontal cortex, the m6A levels and METTL3 expression decrease, accompanied by an increase in FTO and ALKBH5 expression, followed by fluctuating, but statistically insignificant changes in methylation-regulating enzymes over prolonged withdrawal. In the striatum, reductions in m6A levels and METTL3 expression are observed at 4 weeks of withdrawal, preceded by non-significant fluctuations in enzyme expression and the m6A modification levels. In contrast, no changes in the m6A modification levels or the expression of related enzymes are detected in the hippocampus and the cerebellum. Our data suggest that m6A modification and its regulatory enzymes undergo region-specific and time-dependent changes in response to chronic morphine exposure and subsequent withdrawal.
Keywords: messenger RNA; Rats; AlkB Homolog 5, RNA Demethylase; potkani Sprague-Dawley; metylace; mužské pohlaví; methyltransferasy; morphine withdrawal; mozek; adenosin; alfa-ketoglutarát-dependentní dioxygenasa, AlkB homolog 5; Morphine Dependence; morfin; Methyltransferases; krysa rodu Rattus; N6-methyladenosine; gen pro FTO; závislost na morfiu; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Brain; Adenosine; zvířata; RNA, Messenger; abstinenční syndrom; Rats, Sprague-Dawley; FTO; Morphine; morphine; Substance Withdrawal Syndrome; rat brain; Methylation; Male; Animals